'Essex girls' in the comedy club: Stand-up, ridicule and 'value struggles'. (October 2019) - Carter, Adam
This article presents findings from a qualitative study carried out on how audiences of stand-up comedy are entangled in 'value struggles'. It focuses on a group who through classed and gendered ridicule are often drawn as valueless – women from Essex or 'Essex girls'. The article explores how a group of women from Essex negotiate their value in the face of Essex girl–based ridicule, experienced while part of a live comedy audience in a London comedy club. The analysis reveals an ambivalence in how the group utilise and view their 'Essex girl' status, which challenges the view that this is a valueless identification. They oscillate between the joy of revelling in the Essex girl role and disidentification from the shame of this disreputable status. It concludes by highlighting how ridicule does not necessarily perform a disciplinary function and considers if the joy of 'being Essex' has any hope of escaping into everyday life.